Right Atrial Thrombus in a COVID-19 Child Treated Through Cardiac Surgery - Bigdelian, Hamid; Sedighi, Mohsen; Sabri, Mohammad Reza; Dehghan, Bahar; Pourmoghaddas, Zahra; Saleh, Rana; Sherafat, Alireza; Massoumi, Gholamreza; Rezaei, Mohammad Kazem; Shahbazi, Masoud (Frontiers in Cardiovascular Medicine, 2020)
We herein report a case of large intracardiac thrombus in a child with SARS-CoV-2 infection (COVID-19). The diagnosis of COVID-19 was confirmed through HRCT and RT-PCR. Transthoracic echocardiography revealed a large thrombus in the right atrium treated successfully via cardiac surgery. The underlying mechanisms of this thrombus in the COVID-19 infection may be attributed to the hypercoagulation and inflammatory condition incurred by the COVID-19 virus.